Refaat Alareer’s “If I Must Die”: The Death of the Author, the Afterlife of the Tale - Asma Hussein (Arab Studies Quarterly)
This article traces the performative role of tales and storytelling in late Refaat Alareer’s life, career, (creative) writing, activism, and death. It ultimately examines this performativity’s intensification and culmination in Alareer’s Saidian late-style poem “If I Must Die.” The article combines close textual analysis and comparative literary criticism to investigate the intricate relationship between storytelling, mortality, and resistance in Alareer’s poem. Paying attention to nuance, the article examines the poem’s intertextual connections with Claude McKay’s “If We Must Die” (1919) to demonstrate how Alareer transforms storytelling into a powerful mode of cultural survival and a means of transcending physical destruction and preserving collective memory in the face of systematic oppression. Additionally, the research traces Alareer’s evolving conceptualization of storytelling from a personal imperative to a collective form of resistance, culminating in “If I Must Die” whose stylistic and thematic treatment of his impending death anchor his poem locally/nationally, namely in Gaza/Palestine.